The influence of task conditions on side foot-kick accuracy among Swedish first League women`s soccer players - Carlsson, T.; Isberg, J.; Nilsson, J.; Carlsson, M. (Journal of Sports Science & Medicine, 2018)
The purpose of this study was to investigate the influence of the task conditions on 20-m side foot-kick accuracy among Swedish first league women`s soccer players. Twenty-three players performed three side foot-kick tests under different task conditions: stationary ball using match-relevant ball speed (SBRS) and maximal ball speed (SBMS) and a 5-m run with the ball from different approach angles (0°, 30°, and 60°) to a predetermined position, where passing of the ball on the move was executed using match-relevant ball speed (RBRS). With each test, the players performed 30 side-foot kicks, alternating between kicking legs with the aim of hitting a target stick. The accuracy was determined using video analysis. The side foot-kick accuracy was significantly greater for SBRS, compared to RBRS and SBMS. For all three test variables, the preferred leg displayed greater accuracy. The preferred leg`s accuracy was greater for the approach angle of 30° compared to both 0° and 60°. A significant deviation from the target stick was found for the straight-ahead approach, in which the right-foot and left-foot kicks deviated to respectively the left and right of the stick; in contrast, for the approach angle of 60°, the deviation from the target stick was on the opposite side of the approach side for both legs.